Analisis Efektivitas Iklan YouTube Shampo Head & Shoulders Menggunakan Metode Customer Response Index (CRI) - Pradhita Lesveva (Jurnal Dinamika Administrasi Bisnis, 2026)
This study aims to analyze the effectiveness of YouTube advertising for Head & Shoulders shampoo using the Customer Response Index (CRI) method, which consists of five stages: awareness, comprehend, interest, intentions, and action. This study uses a descriptive quantitative method by distributing questionnaires to 101 respondents in the Grand Indraprasta Housing Complex, Block A, Sidoarjo. The results showed that each stage of CRI had a percentage above 50%, with a final CRI value of 47.5%. This value is included in the "quite effective" category based on the CRI measurement scale. These findings indicate that the YouTube advertisement for Head & Shoulders shampoo has been able to attract attention, grow interest, and encourage most consumers to make purchases. However, there are still several stages that need to be improved so that the CRI value can continue to increase. This research is expected to provide input for companies in evaluating the effectiveness of their digital advertising campaigns. The results of the study showed that each stage of CRI had a percentage above 50%, with a final CRI value of 47.5%. This value is included in the "quite effective" category based on the CRI measurement scale. These findings indicate that the Head & Shoulders shampoo YouTube advertisement has been able to attract attention, grow interest, and encourage most consumers to make purchases. However, there are still several stages that need to be improved so that the CRI value can continue to increase.